The Impact of the Coronavirus Pandemic on the Learning Process among Students: A Comparison between Jordan and Turkey - Iman A. Basheti; Razan I. Nassar; İbrahim Halalşah (MDPI AG, 2022)
COVID-19 was declared by the WHO as a pandemic affecting several aspects of human lives. Follow-up investigations showed that the pandemic affected tertiary education. This study was designed to assess the online learning process among students living in Turkey and Jordan during the COVID-19 pandemic. This descriptive cross-sectional study was conducted via an online survey. The survey was followed by a focus group. Data were analyzed using the Statistical Package for Social Science (SPSS). A total number of 214 students participated in this study. Most of the participants were female, single, and undergraduates. Regarding the theory courses, the percentage of Turkish and Jordanian students who evaluated the online learning as 'excellent' or 'very good' or 'good' was greater than that for the practical courses. With regards to the practical training, more than half of the Turkish students (57.5%) ranked their experience in practical training as 'excellent' or 'very good' or 'good', while a lower proportion was reported by Jordanian students (47.7%). During the focus group, the cons of online learning were more numerous than the pros. The tertiary education in Turkey and Jordan was affected during the pandemic.